Eksistensi Hukum Positif dalam Memenuhi Ketentuan Muamalah Pada Praktik Qurban Kontemporer di Indonesia - Harun, Hermanto (Indonesian Journal of Islamic Economics and Business, 2023)
This study aims to examine the phenomenon of contemporary qurban practices and how legal regulations in Indonesia control the practice of animal slaughter to comply with the demands of Islamic muamalah law. the method used is literature study with descriptive normative analysis. In general, there are 3 contemporary qurban models, namely online qurbani and qurbani through mosques. Islamic economic problems that arise are gharar in various aspects especially in quality of animals, slaughtering standard and transaction. Legal regulations in Indonesia include Law No. 18 of 2009, Government Regulation number 95 of 2012, Minister of Agriculture Regulation No. 114 of 2014, and Article 302 of the Criminal Code only covers gharar in terms of quality, health, livestock safety and consumer safety, but has not discussed the gharar aspect of the transaction